RELATIONSHIP BETWEEN PUBLIC PARTICIPATION IN PROJECT PLANNING AND SUSTAINABILITY OF FOREIGN FUNDED WATER SUPPLY PROJECTS IN JUBA CITY: A CROSS SECTIONAL STUDY. - Korsuk, Lui Alex Elisa; Ssendagi , Mohammad (Student's Journal of Health Research Africa, 2024)
Background This study aims to assess the relationship between public participation in project planning and the sustainability of foreign-funded water supply projects in Juba City. Methodology The study employed both quantitative and qualitative approaches to collect data. In total, a sample of 94 respondents participated in the study. Data collection methods used were questionnaires, interviews, and documentary reviews. Quantitative data was coded and entered into SPSS and analyzed using the Pearson correlation coefficient Qualitative data was analyzed using thematic analysis based on the research objectives. Results Pearson’s correlation coefficient for public participation in project planning and sustainability of foreign-funded water Sources in Juba City was r = 0.539**, with a probability value (p = 0.000) that is less than 0 .05 level of significance showing a strong relationship between participation in planning and sustainability of foreign-funded Water Sources Conclusion It was concluded that public participation in project planning has a strong positive relationship with the sustainability of foreign-funded water Sources. This conclusion was based on the Pearson correlation coefficient which is at 539** with a significance level of 0.000. Therefore, if public members are involved in the planning stage such as needs identification, work plan development, and technology selection, there will be improved sustainability of foreign-funded water Sources. Recommendations The study recommends that public members should be involved in drafting work plans to follow while carrying out foreign-funded water Source activities. This will promote community involvement and participation which will enhance ownership and sustainability of foreign-funded water Sources.